HUBUNGAN KETAHANAN KAYU TERHADAP JAMUR DENGAN KERAPATAN DAN PENGKARATAN LOGAM - Sihati Suprapti; Abdurahman; Djarwanto (BRIN Publishing, 2020)
Wood constructions are mostly fastened by metal screw or metal fastener, then corrosion resistance is an importantfactor. Wood natural durability against fungus and its relation to basic density are two other factors affecting woodquality for construction. This paper studies wood natural durability against fungus and metal corrosion in relation todensity of five Riau wood species. Wood samples were tested against fungus using the Kolle-flask method and wooddensity was measured based on DIN-2135-1975 standard. Result shows that Diospyros korthalsiana wood wascategorized as non-resistant (class IV), Tetramerista glabra wood was classified as moderately resistant (class III),while Shorea teysmanniana, Palaquium burckii, and Aglaia argentea woods are grouped into resistant wood(class II). In all wood species, weight lost of heartwood is lower than that of sapwood, but in the same durabilitygroup (moderately resistant). In general, there is a relationship between density and weight loss. The higher the wooddensity is the lower the weight loss. The average of weight loss of metal screwed wood is higher than wood withoutscrews. The highest weight loss was recorded from Palaquium burckii wood which was screwed and exposed toPolyporus sp., while, the highest screw weight loss was recorded from Shorea teysmanniana wood exposed toPycnoporus sanguineus. Rustic enamel was highly recorded from Tetramerista glabra wood, which was exposedinto Tyromyces palustris. Eight species of fungus are moderate and two species are low in capability of decayingwood. The highest decaying ability in corroding metal screws is found in P. sanguineus. The weight of rustic enamelfound in the metal screw caused by four fungus activity of (Chaetomium globosum, P. sanguineus, S. communeand T. palustris) was relatively similar.